2020
DOI: 10.1093/jtm/taaa228
|View full text |Cite
|
Sign up to set email alerts
|

Decreased dengue transmission in migrant worker populations in Singapore attributable to SARS-CoV-2 quarantine measures

Abstract: Background We examined the impact of SARS-CoV-2 social distancing and quarantine policies on dengue transmission in the general and migrant worker populations in Singapore. Methods We utilized all nationally reported dengue cases in the general and migrant worker populations from 1 January 2013 to 31 May 2020. A difference-in-difference identification strategy was used to determine the effects of social distancing and quarantine policies on reported dengue case counts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Of the 26 included studies ( 24 49 ) almost half (12 of 26) were conducted in Asia ( 24 , 26 , 30 , 32 – 35 , 37 , 41 , 44 , 47 , 49 ) and 8 in Europe. Fourteen papers used a quantitative design ( 24 , 27 , 28 , 30 , 32 , 33 , 35 , 36 , 40 , 42 44 , 46 , 48 ), 5 applied mixed methods ( 29 , 31 , 34 , 38 , 45 ) and 23 used primary data sources ( 24 29 , 31 , 32 , 34 , 36 49 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 26 included studies ( 24 49 ) almost half (12 of 26) were conducted in Asia ( 24 , 26 , 30 , 32 – 35 , 37 , 41 , 44 , 47 , 49 ) and 8 in Europe. Fourteen papers used a quantitative design ( 24 , 27 , 28 , 30 , 32 , 33 , 35 , 36 , 40 , 42 44 , 46 , 48 ), 5 applied mixed methods ( 29 , 31 , 34 , 38 , 45 ) and 23 used primary data sources ( 24 29 , 31 , 32 , 34 , 36 49 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most immigrant populations represented in the studies originated from countries in Asia (16 of 26 studies) ( 24 , 26 , 27 , 31 – 34 , 37 , 38 , 41 44 , 47 49 ) and Latin America (8 of 26) ( 25 , 28 , 29 , 38 , 39 , 42 , 44 , 46 ). Other characteristics of the studied populations were often not described in the methodology of the papers: only 9 studies clearly described migrants' length of stay in the host country ( 24 , 27 , 31 , 32 , 37 , 39 , 41 , 43 , 48 ), most of which were long stays (five or more years) and migrants' legal status was not specified in 20 studies ( 26 30 , 32 – 34 , 36 , 37 , 39 , 40 , 42 49 ). Seven studies had a comparison group ( 29 , 30 , 33 , 35 , 36 , 40 , 45 ), most frequently the majority population (6 of 7 studies) ( 30 , 33 , 35 , 36 , 40 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that social restrictions were associated with an increase in DHF cases reported in Singapore. One of the main avenues that could explain this result is the increase in time spent at home addresses due to social distancing policies and the tendency for dengue infection to occur at home rather than at office addresses in Singapore [24].Although workplace infections may surface, it was found that, in many areas, the place of residence is the most common site of vector-borne disease infection rather than the workplace. The concentration of vector breeding sites in the vicinity of residential areas further increases the risk of transmission in these sites compared to workplaces.…”
Section: Discussionmentioning
confidence: 99%
“…Due to extensive investments into vector control, the force of infection is estimated to have rapidly declined from the late 1960s to the mid-1990s, after which the force of infection remained stable [15]. However, persistent outbreaks continue to occur in multi-year cycles [16,17], with the recent 2020 dengue outbreak recording an alltime high of 1,792 weekly cases [18]. This demonstrates the limits of conventional vector control measures such as breeding site elimination and fogging, as well as the importance of evaluating other potential novel vector control strategies, such as Wolbachia.…”
Section: Introductionmentioning
confidence: 99%